PENGARUH METODE MATEMATIKA GASING (GAMPANG, ASYIK DAN MENYENANGKAN) TERHADAP KEMAMPUAN BERHITUNG PERKALIAN SISWA SEKOLAH DASAR - Nurfauziah; Nanang Diana; Hendrawansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to test how students' multiplication calculation skills were influenced by the GASING method. The research methodology chosen was quasi-experimental. All third grade students became the research population. Class III B served as the control group and Class III A served as the experimental group and both became the research sample. The basic random sampling approach was used to conduct sampling. A written test served as a research measurement tool. In the normality test results section, most of the data were not normally distributed, the Wilcoxon test was used in descriptive and inferential statistics used for data analysis. According to the findings, the average pre-test score of the experimental class was 44.71, and its post-test score increased sharply to 87.29. In contrast, the average for the control group increased slightly from 45.00 to 46.35. The pre-test and post-test scores of the experimental class differed significantly (p <0.05) according to the Wilcoxon test, while the shift in the control class was less obvious. These results indicate that there is a significant difference after the application of the GASING method to the experimental class. So, the GASING mathematics method works very well to help third grade students at SDN Monta in improving their multiplication calculation skills.